Pamilya't pag-iisip a toolkit to provide mental health resources to parents of senior high school students from Our Lady of Perpetual Succor College - dela Cruz, Isabella C.
The objective of this study is to determine the underlying problems of UPCFA students who have enrolled themselves in mental health services for the past four years. It was determined that their parents' stigmatized beliefs and the internalization of those beliefs were the primary barriers to help-seeking. When interviewing parents with children 15 years old or older, it was revealed that their stigmatized beliefs came from the lack of mental health discussion and mental health resources 'during their time.' In order to foster understanding and help-giving between the primary stakeholders and their families in regards to mental health issues, those stigmatizing beliefs must be addressed. With this, the question must be: "how might we provide resources for parents so they may be more receptive to their children's mental health status?'